Building Fault-Tolerant Systems with Redundancy and Recovery Mechanisms in Distributed Environments - Prudhvi Chandra, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of fault-tolerant architectures in distributed systems, focusing on redundancy mechanisms and recovery strategies essential for maintaining high availability in mission-critical applications. This article explores various replication patterns, including active-active and active-passive configurations, while examining their implications for system reliability and performance. This article investigates automated failure detection mechanisms, self-healing capabilities, and leader election protocols that form the backbone of resilient distributed systems. Through case studies and practical implementations, it demonstrates how these fault tolerance strategies can be effectively deployed across different scales of distributed environments. This article also addresses the inherent trade-offs between system redundancy, cost efficiency, and consistency guarantees, providing insights into designing robust architectures that can withstand various failure scenarios. It also contributes to the growing body of knowledge in distributed systems design by offering practical guidelines for implementing fault-tolerant mechanisms that minimize service disruptions and reduce manual intervention requirements.
Keywords: Fault Tolerance; Distributed Systems; System Redundancy; Self-healing Architecture; High Availability